2009
DOI: 10.1111/j.1553-2712.2009.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Sulfate versus Placebo for Paroxysmal Atrial Fibrillation: A Randomized Clinical Trial

Abstract: Objectives: The objective was to investigate the efficacy of magnesium sulfate (MgSO 4 ) in decreasing the ventricular rate in emergency department (ED) patients presenting with new-onset, rapid atrial fibrillation (AF).Methods: A double-blinded, placebo-controlled randomized clinical trial was conducted in an adult university hospital. Patients aged ‡18 years with AF onset of less than 48 hours and a sustained ventricular rate of >100 beats ⁄ min were randomized to either intravenous (IV) MgSO 4 10 mmol or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 11 publications
1
27
0
Order By: Relevance
“…Their patient was in shock that was refractory to standard resuscitation therapy but resolved with administration of intravenous lipid emulsion; no adverse events were noted and full patient recovery ensued. Other case reports relate similar hemodynamic improvement in patients with calcium channel blocker overdoses [45,46]. …”
Section: Ile In Non-la Drug Toxicitysupporting
confidence: 54%
“…Their patient was in shock that was refractory to standard resuscitation therapy but resolved with administration of intravenous lipid emulsion; no adverse events were noted and full patient recovery ensued. Other case reports relate similar hemodynamic improvement in patients with calcium channel blocker overdoses [45,46]. …”
Section: Ile In Non-la Drug Toxicitysupporting
confidence: 54%
“…329 Most studies showed a benefit for magnesium in rate control (LOE 1), 295,329,330 although 1 study was neutral for magnesium for rate control (LOE 1). 328 Quinidine has been shown to have greater conversion than sotalol in 2 studies (LOE 1), 331,332 although this was with greater toxicity. Clonidine has rate-controlling properties compared with placebo (LOE 1).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…323,326 Sotalol has consistently been shown to be inferior in conversion compared to other drugs (LOE 1: flecainide 318 and ibutalide 308 ), but equal to amiodarone in 1 study (LOE 1). 325 Most studies showed no conversion benefit for magnesium (LOE 1), 327,328 although 1 meta-analysis showed conversion benefit (LOE 1). 329 Most studies showed a benefit for magnesium in rate control (LOE 1), 295,329,330 although 1 study was neutral for magnesium for rate control (LOE 1).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…The Figure displays trials and meta-analyses that have randomized patients to magnesium in a range of situations, including treatment of acute AF, prevention of AF during cardiac surgery, and facilitation of electric cardioversion. [10][11][12][13][14] Although varying with respect to population and magnesium dosage, they share common features of a small sample size, short follow-up, and disappointing treatment effect.…”
Section: See Article By Rajagopalan Et Almentioning
confidence: 99%